Cancer incidence in vegetarians: results from the European Prospective Investigation into Cancer and Nutrition (EPIC-Oxford). - Key, T; Appleby, P; Spencer, E; Travis, R; Roddam, A; Allen, N (2009)
BACKGROUND: Few prospective studies have examined cancer incidence among vegetarians. OBJECTIVE: We report cancer incidence among vegetarians and nonvegetarians in the European Prospective Investigation into Cancer and Nutrition-Oxford (EPIC-Oxford) study. DESIGN: This was a prospective study of 63,550 men and women recruited throughout the United Kingdom in the 1990s. Cancer incidence was followed through nationwide cancer registries. RESULTS: The standardized incidence ratio for all malignant neoplasms for all participants was 72% (95% CI: 69%, 75%). The standardized incidence ratios for colorectal cancer were 84% (95% CI: 73%, 95%) among nonvegetarians and 102% (95% CI: 80%, 129%) among vegetarians. In a comparison of vegetarians with meat eaters and after adjustment for age, sex, and smoking, the incidence rate ratio for all malignant neoplasms was 0.89 (95% CI: 0.80, 1.00). The incidence rate ratio for colorectal cancer in vegetarians compared with meat eaters was 1.39 (95% CI: 1.01, 1.91). CONCLUSIONS: The overall cancer incidence rates of both the vegetarians and the nonvegetarians in this study are low compared with national rates. Within the study, the incidence of all cancers combined was lower among vegetarians than among meat eaters, but the incidence of colorectal cancer was higher in vegetarians than in meat eaters.